Some acanthocephalans of the family Oligacanthorhynchidae from Peru - Gomez-Puerta, Luis A. (2011)
Four species of acanthocephalan (Oligacanthorhynchidae) were studied. Two species are new geographical records. Additionally, Oligacanthorhynchus carinii and Oligacanthorhynchus major are registered for the first time in Peru.